Fibrinolytic Evaluation of Compounds Isolated from a Marine Fungus Stachybotrys longispora FG216. Issue 11 (14th November 2016) - Guo, Ruihua; Zhang, Yiting; Duan, Dong; Fu, Qiang; Zhang, Xiangyu; Yu, Xiaowei; Wang, Shujun; Bao, Bin; Wu, Wenhui
Abstract: As a part of our continuing work to discover bioactive leading molecules from marine microorganism, ethyl acetate fraction of organic extract of the train Stachybotrys longispora FG216 showed fibrinolytic activity in our primary screen. The bioassay‐guided purification of the active fractions resulted in isolation of a new isoindolone, FGFC2 (1 ) (FGFC2, Fungi fibrinolytic compound 2), together with two known compounds, LL‐Z1272β (2 ) and ergosterol (3 ). The structure of compound1 was elucidated by the spectral analysis of 1D ( 1 H, 13 C) NMR, 2D (COSY, HSQC, and HMBC) and ESI‐MS. Three compounds were evaluated for fibrinolytic activities in vitro . Compared to FGFC1 (EC50 47 µmol/L) as a reference drug, compound1 and ergosterol (3 ) showed moderate fibrinolytic activities in vitro with EC50 values of 108.16 and 156.30 µmol/L, respectively. LL‐Z1272β (2 ) had no fibrinolytic activity. Abstract : Compound1, together with two known compounds, LL‐Z1272β (2 ) and ergosterol (3 ), were isolated from S. longispora FG216. The structure of compound1 was elucidated by the spectral analysis of 1D ( 1 H, 13 C) NMR, 2D (COSY, HSQC, and HMBC) and ESI‐MS. Compounds1 and ergosterol (3 ) showed moderate fibrinolytic activities in vitro with EC50 values of 108.16 and 156.30 µmol/L, respectively.